Cobalt-free layered oxide cathode material

JP7645571B2Active Publication Date: 2025-03-14NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023536359
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-02-21
Filing Date
2022-10-13
Publication Date
2025-03-14
Estimated Expiration
2042-10-13

AI Technical Summary

Benefits of technology

【0017】 また、本出願によれば、リチウム希薄相LiaM2-aO2とリチウム濃厚相Li2M’O3とが一次粒子内で「ナノ複合化」してなるコバルトフリー層状酸化物正極材料が提供される。リチウム希薄相では、リチウム層中のカチオンサイトはすべてリチウムで占められているわけではなく、その大部分は遷移金属原子で占められている一方、遷移金属層におけるカチオンサイトはほとんど遷移金属イオンで占められている。このように、初期材料はリチウム層に遷移金属イオンが大量に存在することにより、充電中に高電圧状態での層状構造を安定させることができ、格子酸素の酸化還元可逆性が大幅に改善される。従って、この新規なコバルトフリー層状酸化物正極材料は、格子酸素の活性を十分に発揮して高い比容量を得るとともに、高い初回クーロン效率とリチウム利用率を実現することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645571000001
    Figure 0007645571000001
  • Figure 0007645571000002
    Figure 0007645571000002
  • Figure 0007645571000003
    Figure 0007645571000003
Patent Text Reader

Abstract

The present invention is a method for producing a lithium-dilute phase Li a M 2-a The present application provides a cobalt-free layered oxide positive electrode material comprising Li2M'O2 and a lithium-rich phase Li2M'O3. The positive electrode material provided by the present application solves to some extent the problems of low energy density, low initial coulombic efficiency, and low lithium utilization rate of the cobalt-free layered positive electrode material under the synergistic action of the lithium-lean phase and the lithium-rich phase. By using such a novel cobalt-free layered positive electrode material as a positive electrode material for a lithium-ion battery, a lithium-ion battery with high energy density can be obtained at a lower cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Cross-reference This application claims the priority of a Chinese patent application filed with the China National Intellectual Property Administration on February 21, 2022, with the application number 2022101576060 and the title of the invention "Cobalt-free layered oxide cathode material", the entire content of which is incorporated herein by reference.

[0002] The present invention relates to the technical field of lithium-ion batteries, and particularly to a cobalt-free layered oxide cathode material and its applications.

Background Art

[0003] In today's society, people's demand for mobile energy storage devices is increasing. Lithium-ion batteries have the characteristics of high energy density and good cycle performance, so the application scale in new energy vehicles and the 3C digital field is expanding. Currently, commercially available cathode materials include lithium iron phosphate, lithium manganate, and ternary layered oxide cathode materials based on nickel cobalt manganese systems.

[0004] Lithium iron phosphate and lithium manganate are inexpensive but have low energy density. On the other hand, currently commercially available layered cathode materials usually contain cobalt, which is a precious metal element, and it is difficult to control the cost. Currently, there are two main directions for cobalt-free layered materials. One is to directly remove cobalt from the conventional nickel cobalt manganese ternary material to prepare a conventional cobalt-free layered material with the chemical formula LiNi x Mn 1-x O2 (0 < x < 1). The other direction is to remove cobalt elements from lithium-rich manganese-based layered oxides to prepare a general cobalt-free lithium-rich layered material with the chemical formula xLiMO2·(1 - x)Li2M’O3 (0 < x < 1, M = Ni + Mn; M’ = Mn).

[0005] Conventional cobalt-free layered materials have lower energy densities than lithium-rich layered oxides, typically with specific capacities less than 220 mAh / g and lithium utilization rates less than 80%. Cobalt-free lithium-rich layered materials have higher specific capacities (greater than 220 mAh / g) but lower initial coulombic efficiency, lower lithium utilization efficiency, and poor multiplier performance. Summary of the Invention [Problem to be solved by the invention]

[0006] The technical problem to be solved by the present invention is to provide a cobalt-free layered oxide positive electrode material. The cobalt-free layered oxide provided in the present application can be used as a positive electrode material for lithium-ion batteries to achieve high initial coulombic efficiency and lithium utilization rate. [Means for solving the problem]

[0007] The present application has been made in view of the above circumstances, and provides a cobalt-free layered oxide positive electrode material represented by the following formula (I): xLi a M 2-a O2·2(1-x) / 3Li2M'O3(I) The cobalt-free layered oxide cathode material has a lithium-dilute phase Li with a layer-like structure in the primary particles. a M 2-a O2 and a lithium-rich phase Li2M'O3, where x is the ratio of the lithium-poor phase to the cobalt-free layered oxide positive electrode material, a is the Li occupancy rate in the lithium layer in the lithium-poor phase, and 0 <x<1、0.5<a<1であり、 M includes A-type ions and M'-type ions, and the ionic radius r of the A-type ions A and the lithium ion radius r Li The relationship is 0.9 <r A / r Li < 1.1, The content of A-type ions is 5% or more of the total ions in M, M' is Mn 4+ , Zr 4+ , Ti 4+ , V4+ 、 Sn 4+ and Ru 4+ provided is a cobalt-free layered oxide cathode material which is one or more selected from the group consisting of

[0008] Preferably, the A-series ions are Ni 2+ , Cu + , Zn 2+ and Fe 2+ and are one or more selected from the group consisting of

[0009] Preferably, the M further includes one or more auxiliary-series ions which are one or more selected from the group consisting of Al 3+ and Cr 3+

[0010] Preferably, the weighted average valence number n of the M ions and M' ions is in the range of 2.9 < n < 3.25.

[0011] Preferably, 0.3 < x < 0.8.

[0012] Preferably, 0.75 < a < 0.95.

[0013] Preferably, the content of the A-series ions is 5% or more with respect to all the ions in M.

[0014] Preferably, the X-ray diffraction spectrum of the cathode material is characterized in that a) an obvious superlattice peak is observed on the right side of the (003) peak; b) the integrated area intensity ratio of the (003) peak and the (104) peak is less than 1.1; c) the (018) peak and the (110) peak have a small degree of splitting and overlap greatly.

[0015] Further, this application provides an electrode including the cobalt-free layered oxide cathode material described in the above form.

[0016] Further, this application provides a lithium ion or lithium metal battery including a cathode and a anode, wherein the cathode is the electrode described above.

[0017] Also, according to the present application, the lithium dilute phase Li a M 2-a A cobalt-free layered oxide cathode material is provided, which is a nanocomposite of Li2M'O2 and the lithium-rich phase Li2M'O3 in the primary particles. In the lithium-lean phase, the cationic sites in the lithium layer are not all occupied by lithium, but are mostly occupied by transition metal atoms, while the cationic sites in the transition metal layer are mostly occupied by transition metal ions. Thus, the presence of a large amount of transition metal ions in the lithium layer of the initial material can stabilize the layered structure at high voltage during charging, and the redox reversibility of the lattice oxygen is greatly improved. Therefore, this novel cobalt-free layered oxide cathode material can fully utilize the activity of the lattice oxygen to obtain a high specific capacity, as well as a high initial coulombic efficiency and lithium utilization rate. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a schematic diagram of a conventional cobalt-free layered cathode material, LiMO2. [Diagram 2] FIG. 2 is a schematic diagram of a typical cobalt-free lithium-rich layered cathode material, xLiMO2·(1-x)Li2M′O3. [Diagram 3] FIG. 3 is a schematic diagram of the cobalt-free layered cathode material xLiaM2-aO2·(1-x)Li2M′O3 provided in the present invention. [Figure 4] FIG. 4 is an X-ray diffraction spectrum of 0.625Li0.945Ni0.582Mn0.473O2·0.25Li2MnO3 provided in Example 1 of the present invention. [Diagram 5] FIG. 5 is a spectrum observed under scanning transmission electron microscope high angle annular dark field imaging (STEM-HADDF) of 0.625Li0.945Ni0.582Mn0.473O2·0.25Li2MnO3 provided in Example 1 of the present invention. [Figure 6]FIG. 6 shows the first cycle charge-discharge curves of 0.625Li0.945Ni0.582Mn0.473O2·0.25Li2MnO3 provided in Example 1 of the present invention. [Figure 7] FIG. 7 is an X-ray diffraction spectrum of 0.7Li0.857Ni0.714Mn0.429O2·0.2Li2MnO3 provided in Example 2 of the present invention. [Figure 8] FIG. 8 is an X-ray diffraction spectrum of 0.8Li0.778Ni0.833Mn0.389O2·0.2Li2MnO3 provided in Example 3 of the present invention. [Figure 9] FIG. 9 is an X-ray diffraction spectrum of 0.5Li0.848Ni0.727Ti0.424O2·0.33Li2TiO3 provided in Example 4 of the present invention. [Figure 10] FIG. 10 is an X-ray diffraction spectrum of 0.6Li0.778Fe0.833Mn0.389O2·0.267Li2MnO3 provided in Example 5 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] In order to further understand the present invention, preferred embodiments of the present invention will be described below in conjunction with examples, but it should be understood that these descriptions are not intended to be limiting on the claims of the present invention, but are merely intended to further illustrate the features and advantages of the present invention.

[0020] In order to further understand the present invention, preferred embodiments of the present invention will be described below in conjunction with examples, but it should be understood that these descriptions are not intended to be limiting on the claims of the present invention, but are merely intended to further illustrate the features and advantages of the present invention.

[0021] The prior art cobalt-free layered oxide positive electrode materials have the disadvantages of low energy density, low first cycle coulombic efficiency, and poor redox reversibility of lattice oxygen. Therefore, the present application provides a novel positive electrode material consisting of a lithium-lean phase and a lithium-rich phase, which has a special two-phase nanocomposite structure in the primary particles, and can greatly improve the energy density, first cycle coulombic efficiency, and lithium utilization rate of the cobalt-free layered positive electrode material. Specifically, the present invention provides a cobalt-free layered oxide positive electrode material represented by the following formula (I): xLi a M 2-a O2·2(1-x) / 3Li2M'O3(I) The cobalt-free layered oxide cathode material has a lithium-dilute phase Li with a layer-like structure in the primary particles. a M 2-a O2 and a lithium-rich phase Li2M'O3, where x is the ratio of the lithium-poor phase to the cobalt-free layered oxide positive electrode material, a is the Li occupancy rate in the lithium layer in the lithium-poor phase, and 0 <x<1、0.5<a<1であり、 M includes A-type ions and M'-type ions, and the ionic radius r of the A-type ions A and the lithium ion radius r Li The relationship is 0.9 <r A / r Li < 1.1, M' is Mn 4+ , Zr 4+ , Ti 4+ , V 4+ , Sn 4+ and Ru 4+ A cobalt-free layered oxide cathode material is disclosed, which is one or more selected from the group consisting of:

[0022] To elaborate on the characteristics of the crystal structure of this novel cobalt-free layered oxide cathode material, it is compared with the crystal structures of conventional layered oxide cathode materials and lithium-rich layered oxide cathode materials. The conventional cobalt-free layered oxide can be represented by the chemical formula LiMO2 (where M is mainly Ni and Mn elements, and Li:M = 1:1). Figure 1 is a schematic diagram of the structure of the conventional cobalt-free layered cathode material. The lithium atom layer and the transition metal atom layer are alternately arranged along the c-axis direction. In the conventional layered oxide cathode material, the lithium atom layer is almost completely occupied by lithium atoms, while the transition metal layer is also almost occupied by transition metal atoms M.

[0023] A general cobalt-free lithium-rich layered oxide cathode material can be represented by the chemical formula xLiMO2·(1 - x)Li2M’O3 (where 0 < x < 1, M is mainly Ni and Mn, and M’ is mainly Mn). The general cobalt-free lithium-rich layered structure is shown in a schematic diagram in Figure 2 and can also be considered as a nanoscale composite of the LiMO2 phase and the Li2M’O3 phase. However, the crystal structure of the LiMO2 phase is similar to the structure of the conventional layered oxide cathode material shown in Figure 1 and the arrangement of transition metal atoms, and no obvious mixing of transition metal and Li is observed. The Li2M’O3 phase is not strictly a layered material, and one-third of the octahedral void positions in its transition metal layer are occupied by Li, and the transition metal M’ and Li are ordered in the transition metal layer. Pure Li2MnO3 is electrochemically inert, but after forming a nanocomposite structure with the LiMO2 phase within the primary particles, it can exhibit the electrochemical activity of lattice oxygen under high voltage (>4.5V). Due to such nanocomposite structural characteristics, the lithium-rich layered oxide can exhibit a high capacity greater than 250 mAh / g.

[0024] The novel cobalt-free layered cathode material proposed by the present invention can be represented by the chemical formula xLi a M 2-a O2·2(1 - x) / 3Li2M’O3. The structure of this novel cobalt-free layered cathode material is shown in a schematic diagram in Figure 3, and the lithium-lean phase Li a M2-a It is considered to be a nano-composite within the primary particles of O2 and the lithium-rich phase Li2M’O3. However, since the crystal structure of the lithium-rich phase Li2M’O3 is consistent with the lithium-rich phase in the cobalt-free lithium-rich layered oxide shown in Fig. 2, this novel material can exhibit the electrochemical activity of lattice oxygen like a general lithium-rich layered oxide material and achieve a high charge-discharge specific capacity. Note that this novel cobalt-free layered oxide cathode material has a special lithium-lean phase xLi a M 2-a O2 (where 0 < a < 1), that is, it should be noted that in the lithium-lean phase, Li:M < 1. In the lithium layer, not all of the cation sites are occupied by lithium, and most are occupied by transition metal atoms, while in the transition metal layer, most of the cation sites are still occupied by transition metal ions. The presence of a large amount of transition metal ions in the lithium layer of the initial material stabilizes the layered structure under high voltage during charging, and significantly improves the redox reversibility of lattice oxygen. Therefore, this novel cobalt-free layered cathode material can fully exert the activity of lattice oxygen to achieve high capacity, and achieve a high initial Coulomb efficiency and lithium utilization rate.

[0025] The lithium-lean phase Li a M 2-a O2 of this application needs to contain three types of cations: Li ions, A-series ions (cations with a radius close to that of Li ions), and M'-type ions (cations with a valence of +4 and likely to form a lithium-rich phase of Li2MO3), and auxiliary cations can be further contained. That is, the metal ion M represents several ions including A-series ions, M'-type ions, and auxiliary cations. However, the radius r A of the A-series ion and the radius r Li of the lithium ion have a relationship of 0.9 < r A / r Li < 1.1. More specifically, the A-series ions are Ni 2+ , Cu + , Zn 2+ and Fe 2+One or more selected from the group consisting of, and the content of A-system ions must not be less than 5% with respect to all ions in M. The auxiliary system ions are Al 3+ and Cr 3+ One or more selected from the group consisting of. The content of tetravalent M' ions in M ions adjusts the average valence state of M ions according to the a value, and usually, the ratio to all M ions is preferably in the range of 20% to 50%. Incidentally, the average valence state of metal ion M is n = (4 - a) / (2 - a).

[0026] M is Ni 2+ 、Cu + 、Zn 2+ 、Fe 2+ etc. and needs to contain one of A-system ions. The reason is that the ionic radius when they form an octahedron coordinated with 6 O ions is closest to the radius of Li + , and it is easy to replace the site of Li + without causing a change in structure, and it is to form a lithium-lean phase Li a M 2-a O2 structure. The ions in M need to contain the transition metal ion M' in the lithium-rich phase that composes with it. This is because it is advantageous for the lithium-lean phase Li a M 2-a O2 and the lithium-rich phase Li2M'O3 to form a complex nano-composite two-phase structure within the primary particles, which promotes the activation of the redox activity of lattice oxygen in the lithium-rich phase and is advantageous for exhibiting the characteristics of high specific capacity.

[0027] In the positive electrode material of the present application, the weighted average valence numbers n of the M ions and M' ions are in the ranges of 2.9 < n < 3.25, 0.3 < x < 0.8, and 0.75 < a < 0.95.

[0028] Regarding the production of the cobalt-free layered oxide positive electrode material described in the present application, after determining the raw materials and the blending ratio of the raw materials, it can be realized according to various conventional material production methods such as the high-temperature solid-phase method and the coprecipitation method in the prior art, and there is no particular limitation in the present application.

[0029] The X-ray diffraction spectrum of the cobalt-free layered oxide cathode material provided in this application is characterized by a) an obvious superlattice peak being observed on the right side of the (003) peak, b) the integrated area intensity ratio of the (003) peak to the (104) peak being less than 1, and c) the (018) peak and the (110) peak being almost overlapped. This indicates that in this novel cobalt-free layered oxide cathode material, a large amount of transition metal ions occupy the position of the Li layer, and the characteristics of the layered structure in which the transition metal ions and Li are arranged in layers in sequence are less obvious.

[0030] The present application also provides an electrode comprising the cobalt-free layered oxide positive electrode material described in the above aspect.

[0031] The present invention still further provides a lithium ion or lithium metal battery comprising a positive electrode and a negative electrode, the positive electrode being an electrode as described in the above embodiments.

[0032] As is well known to those skilled in the art, layered oxide refers to a crystal structure in which oxygen is the structural framework, lithium and transition metals have obvious layered arrangement characteristics in the oxygen octahedral gaps, and the lithium layers and transition metal layers are alternately arranged along the c-axis direction of the unit cell. Lithium utilization rate in layered oxide positive electrode material = content of lithium reversibly desorbed and inserted in positive electrode / total lithium content in positive electrode = specific capacity at first cycle discharge / theoretical specific capacity.

[0033] The cobalt-free layered oxide positive electrode material provided in the present application has a two-phase structure of a lithium-lean phase and a lithium-rich phase, and under the synergistic action of these two phases, the problems of low energy density, low initial coulombic efficiency, and low lithium utilization rate of the cobalt-free layered positive electrode material are resolved to some extent. By adopting such a novel cobalt-free layered positive electrode material as a positive electrode material for a lithium-ion battery, a lithium-ion battery with high energy density can be obtained at a lower cost.

[0034] In order to further understand the present invention, the cobalt-free layered oxide positive electrode material provided by the present invention will be described in detail below in conjunction with examples, but the scope of protection of the present invention is not limited to the following examples. EXAMPLES

[0035] Example 1 The composition is Li 0.945 Ni 0.582 Mn 0.473 The new lithium-rich phase was composed of a lithium-dilute phase with the composition Li2MnO3 and a lithium-rich phase with the composition Li2MnO3. The lithium-dilute phase and the lithium-rich phase accounted for 62.5% and 37.5%, respectively. The chemical formula of this positive electrode material was 0.625Li 0.945 Ni 0.582 Mn 0.473 O2·0.25Li2MnO3(0.375Li 4 / 3 Mn 2 / 3 O2 was approximately 0.25Li2MnO3).

[0036] The coprecipitation method was used as the manufacturing method, in which a mixed solution of NiSO4 and MnSO4 prepared in a stoichiometric ratio of Ni:Mn = 2:3 was dropped into a Na2CO3 solution, the precipitate was filtered and dried to obtain a precursor in which Ni and Mn were uniformly mixed in a stoichiometric ratio, and the precursor was further uniformly mixed with Li2CO3 in a stoichiometric ratio and a high-temperature solid-phase sintering reaction was carried out to obtain the above-mentioned novel cobalt-free layered positive electrode material.

[0037] The X-ray powder diffraction spectrum and the spherical aberration corrected scanning transmission electron microscope spectrum show that the material is mainly an oxide with a layered structure consisting of two phases, lithium-poor and lithium-rich phases, as shown in Figures 4 and 5. Figure 6 shows the typical electrochemical properties of this novel cobalt-free layered cathode material.

[0038] Characterization of the structure and electrochemical testing of this material revealed the following features: (1) The spectrum obtained by X-ray diffraction at a wavelength of 0.154 nm showed a superlattice peak at around 20 degrees. (2) The ratio of the integrated areas of the (003) peak and the (104) peak was less than 1. (3) The (018) peak and the (110) peak almost overlap. (4) When the atomic image of this material was observed under a spherical aberration-corrected transmission electron microscope from a crystal direction perpendicular to the

[0003] orientation, a large number of transition atoms (Ni) appeared in the lithium layer, forming a lithium-dilute phase structure. (5) The initial coulombic efficiency and Li utilization rate both exceeded 90%.

[0039] Example 2 Cobalt-free layered oxide cathode material 0.7Li 0.857 Ni 0.714 Mn 0.429 O2 0.2Li2MnO3

[0040] The coprecipitation method was used as the manufacturing method, in which a mixed solution of NiSO4 and MnSO4 prepared in a stoichiometric ratio of Ni:Mn = 1:1 was dropped into a Na2CO3 solution, the precipitate was filtered and dried to obtain a precursor in which Ni and Mn were uniformly mixed in a stoichiometric ratio, and the precursor was further uniformly mixed with Li2CO3 in a stoichiometric ratio and a high-temperature solid-phase sintering reaction was carried out to obtain the above-mentioned novel cobalt-free layered positive electrode material.

[0041] The XRD spectrum of the positive electrode material obtained above is characteristic of a two-phase composite structure having an obvious lithium-poor phase and a lithium-rich phase, similar to that of Example 1 (shown in FIG. 7).

[0042] Example 3 Cobalt-free layered oxide cathode material 0.8Li 0.778 Ni 0.833 Mn 0.389 O2 0.2Li2MnO3

[0043] The coprecipitation method was used as the manufacturing method, in which a mixed solution of NiSO4 and MnSO4 prepared in a stoichiometric ratio of Ni:Mn = 3:2 was dropped into a Na2CO3 solution, and the precipitate was filtered and dried to obtain a precursor in which Ni and Mn were uniformly mixed in a stoichiometric ratio. The precursor was then uniformly mixed with Li2CO3 in a stoichiometric ratio and a high-temperature solid-phase sintering reaction was carried out to obtain the above-mentioned novel cobalt-free layered positive electrode material.

[0044] As shown in FIG. 8, the XRD spectrum of the positive electrode material obtained above clearly shows the characteristics of a two-phase composite structure consisting of a lithium-poor phase and a lithium-rich phase, similar to Example 1.

[0045] Example 4 Cobalt-free layered oxide cathode material 0.5Li 0.848 Ni 0.727 Ti 0.424 O2 0.33Li2TiO3

[0046] The high-temperature solid-phase method was used for the production, in which Li2CO3, NiCO3, and Ti[OCH(CH3)2]4 were uniformly mixed in a ball mill in a stoichiometric ratio of Li:Ni:Ti = 6:2:3, and then fired at 800°C for 12 hours.

[0047] As shown in FIG. 9, the XRD spectrum of the positive electrode material obtained above clearly shows the characteristics of a two-phase composite structure consisting of a lithium-poor phase and a lithium-rich phase, similar to Example 1.

[0048] Example 5 Cobalt-free layered oxide cathode material 0.6Li 0.778 Fe 0.833 Mn 0.389 O2 0.267Li2MnO3

[0049] The high-temperature solid-phase method was used for the production. Li2CO3, FeO, and MnO2 were mixed uniformly in a ball mill in a stoichiometric ratio and then sintered at 800℃ for 12 hours in an inert atmosphere.

[0050] The positive electrode material obtained above is 0.6Li 0.778 Fe0.833 Mn 0.389 As shown in FIG. 10, the XRD spectrum of O2·0.267Li2MnO3 has the characteristics of a two-phase composite structure, consisting of a clear lithium-poor phase and a lithium-rich phase, similar to Example 1.

[0051] The above description of the embodiments is merely used to understand the method and gist of the present invention. It should be noted that those skilled in the art can make some improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of the claims of the present invention.

[0052] The above description of the disclosed embodiments enables any person skilled in the art to realize or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art. The general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Thus, the present invention is not intended to be limited to these embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A cobalt-free layered oxide positive electrode material represented by the following formula (I): xLi a M 2-a O 2 ・2(1-x) / 3Li 2 M’O 3 (I) The cobalt-free layered oxide positive electrode material has a layer-like structure of lithium-dilute phase Li a M 2-a O 2 and lithium-rich phase Li 2 M'O 3 and where x is the ratio of the lithium-lean phase to the cobalt-free layered oxide positive electrode material, a is the Li occupancy rate in the lithium layer in the lithium-lean phase, and 0<x<1 and 0.5<a<1; M includes A-type ions and M'-type ions, and the ionic radius r of the A-type ions A and the lithium ion radius r Li The relationship is 0.9 < r A / r Li < 1.1, the content of A-based ions is 5% or more based on the total ions in M, M' is Mn 4+ , Zr 4+ , Ti 4+ , V 4+ , Sn 4+ and Ru 4+ The cobalt-free layered oxide positive electrode material is one or more selected from the group consisting of:

2. The A-type ions are Ni 2+ , Cu + , Zn 2+ and Fe 2+ The cobalt-free layered oxide positive electrode material according to claim 1, characterized in that the cobalt-free layered oxide positive electrode material is one or more selected from the group consisting of:

3. The M is Al 3+ and Cr 3+ 2. The cobalt-free layered oxide positive electrode material of claim 1, further comprising one or more auxiliary ions selected from the group consisting of:

4. 2. The cobalt-free layered oxide cathode material according to claim 1, wherein the weighted average valence n of M ions and M' ions is in the range of 2.9<n<3.

25.

5. 2. The cobalt-free layered oxide cathode material according to claim 1, characterized in that 0.3<x<0.

8.

6. 2. The cobalt-free layered oxide positive electrode material according to claim 1, characterized in that 0.75<a<0.

95.

7. 2. The cobalt-free layered oxide cathode material according to claim 1, characterized in that the X-ray diffraction spectrum of the cobalt-free layered oxide cathode material is characterized in that: a) an obvious superlattice peak is observed to the right of the (003) peak; b) the integrated area intensity ratio of the (003) peak to the (104) peak is <1.1; and c) the (018) peak and the (110) peak are little split and largely overlapped.

8. An electrode comprising the cobalt-free layered oxide cathode material according to any one of claims 1 to 7.

9. 10. A lithium ion or lithium metal battery comprising a positive electrode and a negative electrode, the positive electrode being the electrode of claim 8.

Citation Information

Patent Citations

  • La&lt;3+&gt;, Al&lt;3+&gt;, Fe&lt;3+&gt; and F&lt;-&gt; co-doped composite lithium-rich anode material and preparation method thereof

    CN103078104A

  • Positive electrode material as well as preparation method and application thereof

    CN111370666A

  • Li-DEFICIENT MANGANESE COMPLEX OXIDE AND NONAQUEOUS ELECTROLYTE SECONDARY BATTERY

    JP2002063903A

  • Positive electrode material

    JP2013175401A

  • Lithium manganese-containing oxide and method of producing same, cathode active material of lithium ion secondary battery, and lithium ion secondary battery

    JP2014001099A